Pengaruh rasio penambahan gula tebu dan stevia terhadap karakteristik fisikokimia dan organoleptik minuman kesehatan pokak - Hajar, Risa Dewi; Nurhayati, Anis (Universitas Papua, Manokwari, Indonesia, 2025)
Pokak is a traditional Indonesian beverage renowned for its health benefits, typically sweetened with high-calorie sugars like granulated sugar. Excessive consumption of such sweeteners can elevate the risk of obesity and diabetes. Incorporate healthier alternatives like stevia to enhance Pokak's health profile (Stevia rebaudiana B.). This study aims to evaluate the impact of varying ratios of brown sugar cane and stevia on the physicochemical properties (sugar content and viscosity) and organoleptic properties of pokak. Include stevia-to-cane sugar ratios of 60:40, 70:30, 80:20, 90:10, and 100:0. Sugar content was measured using a refractometer, and viscosity was assessed with an Ostwald viscometer. Findings indicate that increasing stevia proportions significantly reduce sugar content and viscosity. The 70:30 stevia-to-cane sugar formulation received the highest organoleptic scores, suggesting an optimal balance between natural sweetness and acceptable thickness. This combination is recommended as a healthier formulation for pokak without compromising consumer acceptance.